2017
DOI: 10.3389/fphys.2017.00562
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Interval Training Leads to Greater Improvements in Acute Heart Rate Recovery and Anaerobic Power as High Volume Low Intensity Training

Abstract: The purpose of the current study was to explore if training regimes utilizing diverse training intensity distributions result in different responses on neuromuscular status, anaerobic capacity/power and acute heart rate recovery (HRR) in well-trained endurance athletes.Methods: Thirty-six male (n = 33) and female (n = 3) runners, cyclists, triathletes and cross-country skiers [peak oxygen uptake: (VO2peak): 61.9 ± 8.0 mL·kg−1·min−1] were randomly assigned to one of three groups (blocked high intensity interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 38 publications
(52 reference statements)
3
29
0
2
Order By: Relevance
“…Training effects on aerobic performance and exercise capacity were assessed as power output (speed) at individual anaerobic threshold (IAT) defined as baseline LA + 1.5 mmol/l (1.5 mmol/l above lactate equivalent; Roecker et al, 1998 ; Dickhuth et al, 1999 ) and maximal running speed. HR recovery defined as HR max - HR 3min was accessed as parameter for the cardiovascular response to the intervention (Okutucu et al, 2011 ; Stöggl and Björklund, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training effects on aerobic performance and exercise capacity were assessed as power output (speed) at individual anaerobic threshold (IAT) defined as baseline LA + 1.5 mmol/l (1.5 mmol/l above lactate equivalent; Roecker et al, 1998 ; Dickhuth et al, 1999 ) and maximal running speed. HR recovery defined as HR max - HR 3min was accessed as parameter for the cardiovascular response to the intervention (Okutucu et al, 2011 ; Stöggl and Björklund, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of cardiac adaptations, recent investigations suggested that metabolic and functional changes in the heart are already detectable after 2 weeks of HIIT (six exercise sessions, 4 – 6 × 30 s of all-out cycling) (Eskelinen et al, 2016 ; Heiskanen et al, 2016 ). Stöggl and Björklund ( 2017 ) analyzed the cardiovascular response in terms of acute HR recovery to a 9-week HIIT intervention in endurance athletes (27 exercise sessions, 4 × 4 min at > 90% HR max running or cycling) and found that HR recovery was improved by 11.2%. Notably, HIIT has also been shown to cause cardiac adaptations in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…HIEC can be performed either at the beginning or at the end of training periods and protocols. In the present study, we applied HIEC to a 9-week program based on High Intensity Interval Training (HIIT), a widely used protocol to improve specific variables of endurance performance [27,28]. It is worth noting that, to date, to the best of our knowledge, no study has tested the effects of the consumption of a commercially available and established BCAA-alanine-CHO based supplement on HIEC over a medium-long endurance training period.…”
Section: Introductionmentioning
confidence: 99%
“…High intensity training (HIT) was demonstrated to be a time efficient alternative to traditional continuous endurance training ( Gibala et al, 2012 ), inducing similar or even superior changes in numerous physiological, performance and health-related markers (e.g., Tabata et al, 1996 ; Helgerud et al, 2007 ; Wisloff et al, 2007 ; Gibala et al, 2012 ; Stöggl and Sperlich, 2014 , 2015 ; Ni Cheilleachair et al, 2017 ). More specifically, HIT was shown to increase both the aerobic and anaerobic capacity ( Tabata et al, 1996 ; Ratel et al, 2004 ; Gibala et al, 2006 ; Stöggl and Björklund, 2017 ) which might be of special interest for ASR as shown above. Finally, it was suggested that HIT might be more enjoyable than continuous endurance training ( Tjonna et al, 2008 ; Bartlett et al, 2011 ; Lambrick et al, 2016 ).…”
Section: Introductionmentioning
confidence: 96%